Blade redesign based on secondary flow suppression to improve the dynamic performance of a centrifugal pump. (23rd June 2023) - Wu, Chengshuo; Pu, Kexin; Shi, Peili; Wu, Peng; Huang, Bin; Wu, Dazhuan
Highlights: Theoretical calculations of blade thickness based on secondary flow suppression. Reduction of pressure pulsation and low-frequency vibration of centrifugal pump. Quantitative analysis of internal secondary flow and outflow uniformity. Correlation between secondary flow suppression and impeller outflow uniformity. Correlation between outflow uniformity and dynamic performance improvement. Abstract: Low-frequency vibration induced by the complex internal flow of centrifugal pumps has been a long-standing challenge in the design of low-vibration pumps. In this paper, a theoretical method of blade thickness calculation is proposed for the passive control of complex flow in centrifugal impellers, and the effects of blade modification based on secondary flow suppression on the dynamic characteristics of model pump are studied by both experimental tests and numerical simulations. The experimental results show that pressure pulsations are affected by flow rate, and their amplitude at the blade passing frequency ( f BPF ) dominates and increases at partial load conditions. The redesigned impeller improves the dynamic performance of the model pump considering the relatively lower pressure amplitude at f BPF and the vibration level at low-frequency band under almost all concerned flow rates. Based on steady-state numerical results, the visualization and quantitative analysis of impeller outflow by introducing the secondary flow coefficient and the static pressure energy coefficient can reveal the correlation between secondary flow suppression and dynamic performance improvement. The proposed blade modification can effectively inhibit the development of secondary flow in the boundary layers and improve the uniformity of static pressure energy distribution of impeller outflow, which results in the reduction of pressure pulsation amplitude at f BPF and subsequent decrease in the low-frequency band vibration level. Meanwhile, pump operation under partial load conditions will intensify the secondary flow in the boundary layers, which contributes to a more non-uniform energy distribution of impeller outflow and deteriorates the dynamic performance of the model pump.